2011
DOI: 10.1063/1.3589370
|View full text |Cite|
|
Sign up to set email alerts
|

Atom probe analysis of interfacial abruptness and clustering within a single InxGa1−xN quantum well device on semipolar (101¯1¯) GaN substrate

Abstract: Pulsed laser atom probe tomography (APT) of InxGa1−xN single quantum well (SQW) grown on semipolar (101¯1¯) GaN orientation estimates the interior atomic composition within the SQW at 6.5±0.7 at. % In, 46.2±0.7 at. % Ga, and 47.3±0.7 at. % N. The atom probe analysis is performed in both “top-down” and “cross-section” orientations. Self-consistent Schrödinger–Poisson simulation employing structural and compositional parameters obtained from APT results estimates the polarization field within the SQW at 720 kV/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…However, Smeeton et al have found that the contrast of HR-TEM images of InGaN/GaN MQWs changes with increasing electron beam exposure time [34]. Further, Galtrey et al [35] and Prosa et al [36] demonstrated no statistically significant deviation from the distribution expected for an In x Ga 1À x N random alloy in In x Ga 1À x N QW with atom probe analysis. According to their reports, the reliable cause of carrier localization in In x Ga 1À x N QW was well width fluctuation at the upper interface between wells and barriers.…”
Section: Resultsmentioning
confidence: 95%
“…However, Smeeton et al have found that the contrast of HR-TEM images of InGaN/GaN MQWs changes with increasing electron beam exposure time [34]. Further, Galtrey et al [35] and Prosa et al [36] demonstrated no statistically significant deviation from the distribution expected for an In x Ga 1À x N random alloy in In x Ga 1À x N QW with atom probe analysis. According to their reports, the reliable cause of carrier localization in In x Ga 1À x N QW was well width fluctuation at the upper interface between wells and barriers.…”
Section: Resultsmentioning
confidence: 95%
“…Specifically, some of the approaches for precipitate analysis include: (i) proximity histograms, (ii) Fourier analysis, and (iii) friends-of-friends analysis. While chemical analysis of a chosen bin size through proximity histograms is a convenient technique for linking spatial features with chemistry and has shown good results [5,19], the definition of the region analyzed is mathematically arbitrary. The region is defined by a user-defined chemical threshold value, and therefore a precipitate is defined largely through assumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the lattice mismatch between InGaN and GaN can also be released in the quantum dots (QDs), which leads to a better electron-hole overlap and increased radiative recombination rates [31]. InGaN/GaN wafers grown nonpolar/ semipolar orientation have eliminated the polarization-induced fields [32]- [34], therefore enabling a complete overlap between electron and hole wave functions and an increase in the optical matrix element [35], [36].…”
mentioning
confidence: 99%